2023
DOI: 10.1186/s40561-023-00249-7
|View full text |Cite
|
Sign up to set email alerts
|

Response to the impact of COVID-19 by health professions education institutions in Africa: a case study on preparedness for remote learning and teaching

Abstract: Background Africa, like other parts of the world, continuously strives to deliver quality health professions education. These efforts are influenced to a larger extent by the socio-economic and cultural context of the region, but also by what happens globally. The global disruption caused by the COVID-19 pandemic in 2020 necessitated the implementation of emergency remote teaching to continue delivering on the mandate of educating future health professionals. The purpose of this research was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…Yasid and Laela demonstrated the efficacy of the ADKAR model, emphasizing the significance of awareness, desire, knowledge, ability, and reinforcement in facilitating successful transformation [73]. Positive awareness of the need for change is crucial for sustainable change in education, as confirmed in [74]. Students', teachers', and administrators' knowledge and experience of necessary programs play a significant role in educational strategies during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 97%
“…Yasid and Laela demonstrated the efficacy of the ADKAR model, emphasizing the significance of awareness, desire, knowledge, ability, and reinforcement in facilitating successful transformation [73]. Positive awareness of the need for change is crucial for sustainable change in education, as confirmed in [74]. Students', teachers', and administrators' knowledge and experience of necessary programs play a significant role in educational strategies during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 97%
“…The prevalence of the digital divide among students and institutions hindered students' ability to adopt e-learning strategies during COVID-19, and most of them were uncertain about learning in a new digital learning environment through LMS [16,41]. The study by Oscar and Marcella [54] revealed that students lacked basic skills in using e-learning systems, and thus, it was difficult for them to balance home responsibilities and online learning tasks during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing online resources for education and socialization can be a valuable tool for families during the COVID-19 pandemic, as it allows children to continue learning and interacting with others while staying at home. Many schools and educational institutions have shifted to online learning platforms like Google Classroom or Zoom to continue providing instruction to students (Chipamaunga et al 2023). Virtual museum tours and field trips are also being offered by many museums, zoos, and cultural institutions, allowing students to explore and learn from home.…”
Section: Utilizing Online Resources For Education and Socializationmentioning
confidence: 99%